A Review of sewerage and drainage systems typologies with case study in Abidjan, Côte d'Ivoire: failures, policy and management techniques perspectives. Issue 1 (31st December 2023) - Ouattara, Zié Adama; Kabo-Bah, Amos T.; Dongo, Kouassi; Akpoti, Komlavi
Abstract: The failure of sewage and drainage systems in SubSaharan African cities is frequent and can be considered as a critical issue, both from an environmental standpoint and in terms of associated maintenance costs. This study analyzes the state of the sanitation systems, the elements behind the failures, the environmental concepts used to classify the problems, and the tools and methodological alternatives for ranking the various management solutions. This research illustrates the causes that contribute to the dysfunctions in the sewage systems of Abidjan as a typical example of sewerage systems management challenges in SubSaharan Africa's large cities. Poor solid waste and wastewater management practices by residents, e.g., illegal dumping of solid waste into the sewers, unauthorized and defective connections to the network, structural dysfunctions related to the age of the network (cracked, denuded, or broken), urban agriculture in the vicinity of the channels, natural phenomena such as erosion, landslides in the undeveloped parts, and the high concentration of vegetation in the network, wholly contribute to the degradation of the network. A variety of decision support systems for the management of the assets of the urban sewage network were presented. The instruments have been categorized based on their capacity and functionality. The operating concept of each of these tools has been outlined, as well as their respective data needs. In addition, the study analyzes challenges related to the usage of existing decision support systems and provides an outlook on future research requirements in this area. This study offers a detailed analysis of the issues of sanitation management and could serve as a reference for other emerging nations in SubSaharan Africa.